2006
DOI: 10.1186/1471-2458-6-282
|View full text |Cite
|
Sign up to set email alerts
|

Association between the metabolic syndrome and its components and gait speed among U.S. adults aged 50 years and older: a cross-sectional analysis

Abstract: Background: To examine the relationship between the metabolic syndrome and its components and gait speed among older U.S. men and women. Whether these associations are independent of physical activity was also explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 38 publications
3
42
0
Order By: Relevance
“…Similar to our results, Angleman et al reported that a high waist circumference was associated with impaired gait speed in adults aged 55-74 years (35). However, Okoro et al found a waist circumference among women to be inversely associated with gait speed impairment and found no such association among men (18). However, they examined waist circumference along with components of the metabolic syndrome, possible intermediaries in the causal pathway between obesity, and loss of physical function (36).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to our results, Angleman et al reported that a high waist circumference was associated with impaired gait speed in adults aged 55-74 years (35). However, Okoro et al found a waist circumference among women to be inversely associated with gait speed impairment and found no such association among men (18). However, they examined waist circumference along with components of the metabolic syndrome, possible intermediaries in the causal pathway between obesity, and loss of physical function (36).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, we hypothesized that the association between obesity and gait speed may also vary by race=ethnicity. However, among the previous studies of obesity and gait speed, race=ethnicity differences were either not examined (17,18,22,23) or not observed (20,21). The purpose of this study was to examine the relationship between obesity, measured by body mass index (BMI) and waist circumference, and habitual gait speed in order to determine whether this relationship varies by race=ethnicity.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Mobility is also critical to maintaining independence and social interaction in the later years of life and is an essential aspect of quality of life. Persons with poor lower extremity function, slow gait speed, and particularly those with walking disability, are at higher risk of chronic disease, hospitalization, and death than their peers who walk normally 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Results describe that there is a positive correlation between peripheral vestibular disorders and vascular changes associated to atherosclerosis. An epidemiological study from the National Health and Nutrition Examination Survey which included 1,685 individuals with age equal to or higher than 50 years, observed a gait problem in women with low levels of HDL-cholesterol and a greater frequency of abdominal obesity 10 . Other studies also describe an association between gait disorders and abdominal obesity 11,12 .…”
Section: Introductionmentioning
confidence: 99%